The thankful book - Parr, Todd (New York : Megan Tingley Books, 2012)
Easy-to-read text encourages the reader to find something every day for which to be thankful, from underwear that is just the right size to birthday cakes and the wishes they bring.
Keywords: Gratitude -- Fiction